Stomatocyst of Spiniferomonas minuta Nicholls and the extent of morphological diversity of stomatocysts among species of the genus Spiniferomonas E. Takahashi (Chrysophyceae) - Bessudova, Anna Y.; Firsova, Alena D.; Likhoshway, Yelena V. (Phytotaxa, 2025)
Silica‑scaled chrysophytes can form siliceous stomatocysts in addition to scales and bristles, but the morphology of these stomatocysts is known for only a few species. Using scanning electron microscopy, we observed numerous plate-scales of the rare species Spiniferomonas minuta on the surface of stomatocyst Stomatocyst 331 Firsova & Likhoshway, whose species identity had been previously unknown. The stomatocyst is primarily spherical to broadly obovate, has an asymmetrically positioned conical pore, and its surface bears conulae, verrucae, and echinate spines. This morphotype was found in the southern part of Lake Baikal in October at a water temperature of 8.8 °C and pH 8.2. A comparative analysis of known stomatocyst morphotypes in Spiniferomonas species revealed considerable morphological diversity.